Tracking spasticity dynamics in hemiparetic stroke survivors following cyproheptadine administration: a pilot study using controlled varying tendon indentation depths - Bae, Sungjin; Chardon, Matthieu K.; Roth, Elliot J.; Rymer, William Z.; Suresh, Nina L. (Frontiers in Stroke, 2025)
This study evaluates the potential of the Linmot® tapper as a precise tool for tracking spasticity changes in hemiparetic stroke survivors following cyproheptadine HCl administration. Spasticity, a significant health concern among stroke survivors, is characterized by increased muscle tone due to upper motor neuron dysfunction. Conventional clinical assessments, such as the Modified Ashworth Scale (MAS), often lack the sensitivity to accurately monitor treatment. In this study, we utilized the Linmot® tapper to assess the stretch reflex threshold (SRT) in three stroke survivors and one control subject by progressively altering tendon indentation to change muscle length. The SRT was defined as the indentation depth at which consistent reflex responses of the biceps brachii were observed, as indicated by reflex force or rectified integrated EMG (RIEMG) signals. Measurements were taken at baseline and at 2, 4, and 6 h after drug administration. Results showed significant increases in SRT following cyproheptadine administration, indicating reduced motor neuron excitability and highlighting the drug's effect on spasticity. Both reflex force and RIEMG data consistently captured these changes, while MAS grades remained unchanged. The high correlation between SRTs derived from force and EMG further supports the tool's accuracy in detecting subtle neuromuscular changes. These findings highlight that the Linmot® tapper offers a precise, quantitative method for monitoring spasticity dynamics, providing a more accurate alternative to conventional clinical assessments and demonstrating potential for enhancing stroke rehabilitation strategies.